Hukum adat dan hukum Islam di Indonesia : refleksi terhadap beberapa bentuk integrasi hukum dalam bidang kewarisan di Aceh - Syahrizal, 1970- (Batuphat, Lhokseumawe, Nanggroe Aceh Darussalam : Yayasan Nadiya, 2004)
Integration of adat law and Islamic law relating to inheritance in Aceh, Indonesia.
Originally presented as the author's thesis (doctoral--Universitas Padjadjaran, Bandung, 2001) under title: Hubungan antara hukum adat dan hukum Islam dalam masalah kewarisan di Aceh.
Includes bibliographical references (p. 343-360) and index.
Keywords: Inhertance and succession -- Indonesia -- Aceh; Inheritance and succession (Islamic law) -- Indonesia -- Aceh; Adat law -- Indonesia -- Aceh; Inheritance and succession (Adat law)